CLIC2 regulates immunosuppression and macrophage differentiation in genomically stable gastric cancer - Viviana Longo; Pellegrino Mazzone; Giovanni Calice; Pietro Zoppoli; Giuseppina Di Paola; Giuseppe Cesta; Margherita Luongo; Claudia Sabato; Sabino Russi; Simona Laurino; Tiziana Notarangelo; Giuseppe Patitucci; et al. (Biology Direct)
Abstract Chloride intracellular channels (CLICs) are a family of six evolutionarily conserved proteins with diverse functions. Previously, we identified CLIC2, as the fifth-ranked master regulator associated with diffuse-type gastric cancer (dGC) showing increased expression in tumors. Here we used bulk, as well as single cell sequencing datasets of dGC, to demonstrate for the first time a direct association of CLIC2 with the microsatellite stable GC and, furthermore, the expression of CLIC2 in macrophages (MCs), and endothelial cells (ECs) populating gastric tissue. We generated CLIC2 knock-out THP-1 monocytic cells (THP-1CLIC2_KO) determining that while CLIC2 deletion had no observable effect on monocytes, THP-1CLIC2_KO macrophages exhibited significant morphological changes, including increased membrane protrusions, and upregulated expression of CD11b, CD11c, CD80, and CD86 markers. Furthermore, cytokine secretion profiling of THP-1CLIC2_KO differentiated cells revealed elevated secretion of CCL8, alongside reduced secretion of IL-1β, IL-6, and osteoprotegerin (OPG). Additionally, we observed increased phosphorylation of Shp1 phosphatase with the concomitant absence of Stat3 phosphorylation, which impaired downstream signaling, in line with the evidence that Clic2 interacts with both Shp1 and Stat3. Based on these findings, we suggest that CLIC2 plays a pivotal role in regulating monocyte-to-macrophage differentiation by modulating the Stat3 signaling pathway, thus enhancing gastric cancer progression by establishing a tumor-permissive microenvironment.